Disposal of E-Waste: Government Agencies’ Perspective - Suziyana, Mat Dahan; Wan Adibah Hasyimah, Wan Omar; Mohd Yusof, Taib (AIP Publishing, 2024)
The widespread consumptions of electronic products over the years has resulted in the rapid generation of growing range of e-waste, or electronic waste. The inappropriate treatment of e-waste can cause serious unfavourable impacts to human and environmental sustainability due to the hazardous substances within the e-waste. The focus of this study is on somewhat under-emphasised group of electronic goods users that contribute significantly to e-waste: government agencies. Even though they create a high rate of e-waste, the disposal methods of e-waste that they deploy are not well understood. Hence, this study is to provide such an understanding. This study draws quantitative data from 112 agencies in Terengganu, Malaysia, obtained by means of a questionnaire-based survey. The findings revealed that most agencies are either store their end-of-life electronic items at their office or discard their e-waste together with other general office wastes. This study suggests that more extensive of similar descriptive research remains to be performed, covering government agencies in all states of Malaysia to draw a more significant conclusion of the adopted approaches in managing their e-waste.